2023
DOI: 10.1177/0193841x231166741
|View full text |Cite
|
Sign up to set email alerts
|

Go for Economic Transformation and Development in China: Financial Development, Higher Education, and Green Technology Evolution

Abstract: Technology innovation is the key driving force in achieving economic transformation and development. Financial development and the expansion of higher education can promote technological progress primarily by easing financing constraints and improving the level of human capital. This study examines the impact of financial development and higher education expansion on green technology innovation. It conducts an empirical analysis by constructing a linear panel model and a nonlinear threshold model. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Lastly, the role of human capital in green electricity is statistically signifi cant but negatively related to the transition to green electricity. Generally, the positive impact is that human capital eff ectively encourages economic development by innovating green and efficient technologies (Paramati et al, 2022;Liu et al, 2023;Zhou et al, 2024). However, the estimated results indicate that certain factors or reasons could negatively infl uence green transition.…”
Section: Regression Investigationmentioning
confidence: 98%
“…Lastly, the role of human capital in green electricity is statistically signifi cant but negatively related to the transition to green electricity. Generally, the positive impact is that human capital eff ectively encourages economic development by innovating green and efficient technologies (Paramati et al, 2022;Liu et al, 2023;Zhou et al, 2024). However, the estimated results indicate that certain factors or reasons could negatively infl uence green transition.…”
Section: Regression Investigationmentioning
confidence: 98%
“…The current green revolution in the economy and the realization of climate goals require industries and the agricultural sector to take actions that place a low burden on the environment [10]. They will enable them to adapt to climate change and introduce low-carbon technologies.…”
Section: Introductionmentioning
confidence: 99%
“…It requires channeling the human and financial capitals in a target way. The study by Zhou et al (2023) has shown that channeling the investments in promoting higher education is a primary step towards boosting green technological innovations in China. The study also found that impact of financial development on green technological innovations is nonlinearly conditional upon the degree of higher education.…”
mentioning
confidence: 99%